2020
DOI: 10.1508/cytologia.85.71
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Examination of Human Peripheral Blood Lymphocytes Cryopreserved after Gamma Irradiation: A Pilot Study

Abstract: For the assessment of radiation-induced damage in human cells, the frequency of chromosomal aberrations, especially that of dicentric chromosomes in peripheral blood lymphocytes, has been used as the measure in biodosimetry. Considering mass-casualty radiological incidents, it is hoped to preserve part of the blood specimens to be examined at an appropriate time after the medical triage process. In this study, the potential usefulness of lymphocytes cryopreserved for longer than one year was assessed as a pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…With the comet assay, a similar response to γ-radiation was found between frozen whole blood and frozen isolated PBMCs A c c e p t e d M a n u s c r i p t (Ladeira et al 2019). Analysis of chromosomal aberrations in 1.5 year frozen PBMCs after 2 Gy γ-irradiation also revealed no significantly different result compared to fresh blood samples (Suto et al 2020). An earlier study of our group showed that X-rays induced MN in frozen isolated PBMCs were significantly higher than in fresh isolated PBMCs.…”
Section: Accepted Manuscript Discussionmentioning
confidence: 63%
“…With the comet assay, a similar response to γ-radiation was found between frozen whole blood and frozen isolated PBMCs A c c e p t e d M a n u s c r i p t (Ladeira et al 2019). Analysis of chromosomal aberrations in 1.5 year frozen PBMCs after 2 Gy γ-irradiation also revealed no significantly different result compared to fresh blood samples (Suto et al 2020). An earlier study of our group showed that X-rays induced MN in frozen isolated PBMCs were significantly higher than in fresh isolated PBMCs.…”
Section: Accepted Manuscript Discussionmentioning
confidence: 63%
“…To study the regulation of chromatin dynamics in living cells, imaging strategies to detect a specific genomic site or gene locus has been developed Matsunaga 2016, Hirakawa andMatsunaga 2016). Classical imaging methods, such as fluorescent in situ hybridization (FISH), have excellent signal-to-noise ratios but require pre-treatment of cells, such as the cell fixation and the DNA denaturation, which prevents the capture of chromatin dynamics (Matsunaga 2016, Matsunaga and Matsunaga 2017, Kikuchi and Iwamoto 2020, Shafiee et al 2020, Suto et al 2020, Widarmi et al 2020, Amiad-Pavlov et al 2021, Hondo and Azumi 2021, Suto et al 2021, Wang and Sheng 2022. The integration of chromatin labeling with live cell imaging can directly observe the dynamics of the specific chromatin in a nucleus.…”
mentioning
confidence: 99%
“…Genomic DNA is constantly exposed to exogenous stimuli, such as ultraviolet (UV) or gamma radiation (Takahashi et al 2019, Suto et al 2020, environmental pollution (Basu et al 2019, Hani et al 2020, artificial chemicals (Ergin et al 2020, Gantayat et al 2020, chemotherapeutic drugs (Gupta et al 2020), dietary genotoxins, and endogenous stimulants during physiological cellular processes (Jackson and Bartek 2009, Paigen and Petkov 2010, Diaz and Pecinka 2017, Tubbs and Nussenzweig 2017, Toyoda and Matsunaga 2019, Marques et al 2020, Mingard et al 2020, Nishioka et al 2020. These stimulants are known to induce approximately 70,000 lesions every day in each human cell, including single-strand breaks (SSBs) and double-strand breaks (DSBs), which are essentially fixed via various DNA repair pathways (Kunkel 2015, Tubbs andNussenzweig 2017); however, sometimes DNA damage is not repaired correctly, and the accumulation of these unrepaired damages is known to cause various pathological conditions, such as premature aging, cancer, and neurological disorders (Lord and Ashworth 2012, Baranello et al 2014, Canela et al 2016, González and Plasencia 2017.…”
mentioning
confidence: 99%